RESEÑA de : Domínguez Rey, Antonio. Ciencia, conocimiento y lenguaje : Ángel Amor Rubial (1869-1930). Madrid : Spiralia Ensayo/UNED, 2007 - Jiménez Redondo, Manuel (Investigaciones Fenomenológicas, 2008)
_